The effect of antitumor trans-[PtCl2(E-iminoether)2] on B-->Z transition in DNA - Zaludová, R; Natile, G; Brabec, V (Anti-cancer drug design, 1997)
The B-->Z transition of DNA modified by platinum(II) complexes has attracted considerable interest because of a possible relationship with the molecular mechanism of antitumor activity of these metal-based compounds. Until recently it was generally accepted that the cis geometry of leaving groups in the bifunctional platinum(II) complexes should be therapeutically active. This paradigm had to be abandoned recently due to the finding that several analogues of clinically ineffective trans-diamminedichloroplatinum(II) (transplatin) exhibit antitumor activity. One of these therapeutically active trans compounds is trans-dichlorobisiminoetherplatinum(II) (trans-EE) [iminoether = E-HN = C(OMe)Me]. In view of the fact that DNA is the main pharmacological target for platinum(II) complexes and that these complexes attack preferentially guanine residues in DNA, it is of interest to examine the effect of iminoether platinum(II) complexes on the conformation of double-stranded poly(dG-dC) and its synthetic analogues. As these polymers can undergo the B-->Z transition, we have investigated in detail the effect of trans-EE and its cis isomer (cis-EE) on this conformational transformation using different techniques. They include circular dichroism spectroscopy, Raman spectroscopy and immunochemical assay employing specific antibodies against Z-DNA. It has been shown that cis-EE somewhat facilitates the B-->Z transition induced by increasing NaCl concentration and radically lowers its cooperativity. The polymers modified by cis-EE at low or high salt concentrations have been found to adopt distorted conformations which belong to the B and Z families respectively. Thus, cis-EE affects the B-->Z transition in DNA in a way similar to antitumor cis-diamminedichloroplatinum(II) (cisplatin). On the other hand, trans-EE was found to affect B-->Z transition (its cooperativity or the NaCl concentration corresponding to the midpoint of the salt-induced transition) only slightly. This behavior of trans-EE was, however, fundamentally different from that of clinically ineffective transplatin, which hinders B-->Z transition and lowers its cooperativity. The different effects of trans-EE on the B-->Z transition in comparison with the effects of cisplatin, transplatin and monofunctional chlorodiethylenetriamineplatinum(II) chloride are consistent with a unique DNA binding mode of this new antitumor trans compound, which might be associated with its unexpected biological efficacy.
Keywords: Cisplatin; Antibody Affinity; cisplatina; konformace nukleové kyseliny; kompetitivní vazba; stereoizomerie; ELISA; Enzyme-Linked Immunosorbent Assay; Nucleic Acid Conformation; Spectrum Analysis, Raman; afinita protilátek; Binding, Competitive; DNA; Ramanova spektroskopie; Stereoisomerism